A Study of the CryoTel® DS 1.5 Cryocooler for Higher Cooling Capacity. Issue 1 (November 2015) - Kim, Yongsu; Wade, Jimmy; Wilson, Kyle
Abstract: The CryoTel ® DS 1.5 is a split type Stirling cryocooler which was developed by Sunpower for systems requiring compact size, high efficiency, and high reliability. The DS 1.5 has a nominal lift of 1.5 watts at 77 K with 30 watts of input power. The cooler design includes gas bearings on the pistons and displacer for non-contact operation, and achieves low vibration by using dual-opposed pistons inside the wave generator, and a passive balancer on the cold head to offset the displacer motion. The efficiency of the DS 1.5 is ranked highly compared to other cryocoolers at 14.2% Carnot efficiency, but there are many customers who want more lift with the same size and reliability. Therefore, Sunpower performed a study on the feasibility of maximizing the lift of the DS 1.5 without increasing its size. This paper describes the analysis and test results of increasing the cooler power density by using a higher operating frequency and charge pressure. Prototype testing showed good agreement with the model. Testing performed at various frequencies and charge pressures with a few internal component changes resulted in a maximum lift of 2.1 watts with an input power of 43 watts, achieving 13.9% of Carnot. The prototype high-capacity DS 1.5 achieved 0.6 watts more lift with only a slight decrease in efficiency, and with less than 0.2% cooler mass increase. The impact on the cooldown time on a thermal mass system was tested and the cool-down time was 37% faster while consuming less input energy during that time. Sunpower plans to build more units to gain a broader range of performance data and will then decide whether to proceed with a commercial product.